2023
DOI: 10.1002/yea.3852
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of dung beetle‐associated yeasts from pristine environments of Botswana

Abstract: Yeast-insect interactions are increasingly becoming an attractive source of discovery for previously unknown, unique, diverse, and industrially relevant yeast species. Despite a wealth of studies that have recently focused on yeasts in symbiotic association with Hymenopteran insects, yeasts associated with Coleopteran insects, such as lignocellulosic-rich dung-dependent beetles, remain poorly studied. Trends in yeast discovery suggest that species richness and diversity can be attributed to the ecological nich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…S. ligniputridi and P. guehoae were detected in the foregut of both O. barnabita larvae and their galleries. S. ligniputridi has been found in rotten wood [82] and P. guehoae has been isolated from dung beetles [83].…”
Section: Discussionmentioning
confidence: 99%
“…S. ligniputridi and P. guehoae were detected in the foregut of both O. barnabita larvae and their galleries. S. ligniputridi has been found in rotten wood [82] and P. guehoae has been isolated from dung beetles [83].…”
Section: Discussionmentioning
confidence: 99%
“…guilliermondii, C. humilis, and S. cerevisiae were the most frequently isolated yeasts. Nwaefuna et al (2023) reported the yeast communities associated with dung beetles inhabiting pristine environments in Botswana. The authors obtained a total of 97 phylogenetically diverse yeast isolates, representing 19 species belonging to 11 genera.…”
Section: African Tropical Forestsmentioning
confidence: 99%